Chronic Whiplash Syndrome: Associated Disorders and Physiotherapy Management – A Literature Review - Koumantakis, George A.; Tsiampokalou, Angeliki; Chrysagis, Nikolaos; Grammatopoulou, Eirini; Tatsios, Petros (British Journal of Healthcare and Medical Research, 2021)
Purpose: The purpose of the current literature review is to present the Whiplash Associated-Disorders through diagnosis, scales, physical examination and to identify the most suitable physiotherapy management of these conditions. The long-term effectiveness of physiotherapy interventions is also examined. Methods: Sixteen randomized controlled trials (RCTs) and seven case-control and cohort studies related to chronic WAD fulfilled the inclusion and exclusion criteria. The design, diagnosis, population, methodology, results, methodological quality and physiotherapy management were examined. The PEDro Scale and the Newcastle-Ottawa Scale were used for the examination of the methodological quality. Results: The methodological quality of the studies used, were high. Significantly important on minimizing the symptoms of chronic WAD were the combination of Exercise therapy & Advice both at 6 and 12 months follow up. Other interventions such as Exercise therapy, Interdisciplinary approach and Multimodal physiotherapy treatment, Spinal Manual therapy and Advice were not equally effective in the long-term. Conclusion: The most suitable intervention for the physiotherapy management of chronic WAD, with long-term effectiveness was the combination of Exercise & Advice, which was established with various outcome measures, such as NDI, VAS, NRI and SF-36. On the contrary, Exercise therapy, Interdisciplinary approach and Multimodal physiotherapy treatment, Spinal Manual therapy and Advice were not that effective on minimizing the symptoms of chronic WAD in the long-term.